A generalzation of Ostrowski-gruss type inequality for first differentiable mappings - Zafar, Fiza (Tamsui Oxford Journal of Mathematical Sciences)
In this paper, we improve and further generalize some Ostrowski-Gruss type inequalities involving first differentiable functions and apply them to probability density functions, generalized beta random variable and special means.